Method for improving efficiency of anaerobic membrane bioreactor and relieving membrane pollution by pyrolytic carbon

By adding pyrolysis of honeycomb carbon material (SC) obtained by pyrolysis to the anaerobic membrane bioreactor, the problems of microbial community stability and membrane pollution are solved, the anaerobic digestion efficiency and methane yield are improved, and the service life of the membrane module is extended.

CN119612758AInactive Publication Date: 2025-03-14ANHUI UNIV

Patent Information

Application Number
CN202411790101.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The stability of the microbial community under low temperature or fluctuating operating conditions is affected, resulting in a decrease in reactor efficiency and faces membrane pollution problems, affecting the overall efficiency of the system.

Method used

In the startup stage of the anaerobic membrane bioreactor, carbon material (SC) with a honeycomb-like structure obtained by heating and pyrolysis by sodium citrate as a conductive material, promoting electron transfer between microorganisms and microorganism enrichment.

Benefits of technology

It significantly improves the anaerobic digestion efficiency, extends the service life of membrane modules, slows down membrane pollution, and improves methane production and resource utilization efficiency of sewage treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612758A_ABST
    Figure CN119612758A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the efficiency of an anaerobic membrane bioreactor and relieving membrane pollution by pyrolytic carbon, in the starting stage of the anaerobic membrane bioreactor, a conductive material SC is added into the reactor for anaerobic digestion reaction, and the conductive material SC is a carbon material which is obtained by heating and pyrolyzing sodium citrate and has a honeycomb structure. According to the scheme, SC is used as a conductive carrier in the anaerobic membrane bioreactor, and the anaerobic digestion reaction is promoted by combining the synergistic effect of a magnetic stirring system and a gas circulating pump. Experimental results show that the conduction characteristic of SC can effectively promote electron transfer and enhance the metabolic activity of anaerobic microorganisms, so that the degradation capacity of pollutants is improved, membrane pollution is effectively slowed down, the service life of a membrane assembly is remarkably prolonged to 6 times of the original service life, and the yield of CH4 is increased to 1.39 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for enhancing the efficiency of an anaerobic membrane bioreactor, belongs to the technical field of membrane bioreactors, and particularly relates to a method for enhancing the efficiency of an anaerobic membrane bioreactor with pyrolytic carbon and alleviating membrane pollution. Background Art

[0002] Anaerobic digestion is an important and effective pollutant-to-energy technology, which is widely used in the field of wastewater treatment. Upflow anaerobic sludge blanket reactor (UASB) and continuous stirred reactor (CSTR) are the most commonly used reactor types for anaerobic digestion technology. Although these reactors have their own advantages in practical applications, there are also some problems that need to be solved. Under low temperature or fluctuating operating conditions, the stability of the microbial community of the UASB reactor is affected, resulting in reduced reactor efficiency. When dealing with high organic loads, the CSTR reactor faces problems of sedimentation separation and sludge deposition. Under stable operating conditions, long-term operation leads to uneven material flow inside the reactor, which in turn affects the output of CH4 and digestion efficiency.

[0003] As an emerging sewage treatment technology, anaerobic membrane bioreactor (AnMBR) combines the advantages of anaerobic digestion and membrane separation, and can effectively remove organic matter and realize sewage resource utilization. Compared with traditional reactors, AnMBR has significant advantages in effluent quality, solid matter separation capacity, reaction rate and adaptability. In recent years, the research on AnMBR has gradually increased, mainly focusing on membrane fouling control, reactor design and its application in different sewage treatment. AnMBR still faces some technical bottlenecks, especially membrane fouling. Membrane fouling not only reduces the flux of the membrane, but also increases the cleaning frequency and maintenance cost, thus affecting the overall efficiency of the system. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and provide a method for improving the efficiency of anaerobic membrane bioreactors and alleviating membrane fouling by using pyrolytic carbon, which has the characteristics of promoting interspecies electron transfer, enriching microorganisms and alleviating membrane fouling, and can effectively improve the efficiency of anaerobic digestion, extend the service life of membrane components, and thus improve the overall efficiency of anaerobic membrane bioreactors.

[0005] In order to achieve the above objectives, the present invention provides a method for improving the efficiency of an anaerobic membrane bioreactor and alleviating membrane fouling by using pyrolytic carbon. During the startup phase of the anaerobic membrane bioreactor, a conductive material SC is added into the reactor to carry out anaerobic digestion reaction. The conductive material SC is a carbon material with a honeycomb structure obtained by pyrolyzing sodium citrate at a high temperature.

[0006] Preferably, the effective working volume of the anaerobic membrane bioreactor is 3.5 L, and the internal temperature is maintained at 35-37°C.

[0007] Preferably, the amount of the conductive material SC added is 0.5 of the volume of the sludge mixed liquid inside the reactor, and the moisture content of the sludge is 86.29%.

[0008] Preferably, the heating rate of the sodium citrate pyrolysis is 5°C / min, and the pyrolysis is carried out for 2-4 hours after being heated to 600°C, and then cooled to room temperature at a cooling rate of 5°C / min.

[0009] Preferably, after the conductive material SC is obtained by pyrolysis at elevated temperature, it is first washed with a hydrochloric acid solution having a concentration of 0.8-1.2 mol / L, then washed with deionized water until neutral, and then dried.

[0010] Preferably, the method uses artificial simulated wastewater as the influent reaction matrix, the artificial simulated wastewater is composed of NH4Cl, KH2PO4, NaHCO3 and trace elements, and is refrigerated and stored, and the carbon, nitrogen and phosphorus ratio of the artificial simulated wastewater is 100-300:5:1.

[0011] Preferably, a self-made flat membrane assembly is arranged inside the anaerobic membrane bioreactor, the membrane material is polyvinylidene fluoride, the average pore size is 0.05 μm, and the effective filtration area is 0.0288 m 2 .

[0012] Preferably, the anaerobic membrane bioreactor is equipped with a magnetic stirring system and a gas circulation system for coordinated operation.

[0013] The technical solution of the present invention may include the following beneficial effects:

[0014] Introducing SC as a conductive material in anaerobic membrane bioreactors can not only effectively reduce membrane fouling, but also extend the service life of membrane components by 6 times. The preparation process of SC is simple and low-cost, and adding an appropriate amount can achieve significant treatment benefits. Its good conductivity promotes electron transfer between microbial species, thereby increasing methane production by 1.39 times, significantly improving the anaerobic digestion efficiency of microorganisms, and realizing resource utilization of sewage treatment.

[0015] The present invention utilizes gradient temperature rise pyrolysis technology to convert sodium citrate into SC with a honeycomb structure, and adds the SC into a sewage anaerobic treatment system, which can significantly increase the methane production of the microbial anaerobic digestion system. The reason is mainly attributed to the good biocompatibility, rapid mass transfer capacity and electron transfer capacity of SC. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a schematic diagram of the structure of the anaerobic membrane bioreactor used;

[0017] Figure 2The figures are scanning electron microscope images of the prepared SC, scanning electron microscope images of the anaerobic sludge inside the blank group (R1) and the carbon addition group (R2) of the anaerobic membrane bioreactor, and scanning electron microscope images of the membrane component materials, wherein (a) is a scanning electron microscope image of the SC prepared in step (1) of Example 1, (d) is a scanning electron microscope image of the membrane material used in Example 2, (b) and (e) are scanning electron microscope images of the anaerobic sludge inside the reactors when R1 and R2 were operated for 40 days in Example 2, respectively, and (c) and (f) are scanning electron microscope images of the anaerobic sludge inside the reactors when R1 and R2 were operated for 120 days in Example 2, respectively;

[0018] Figure 3 The gas adsorption analysis diagram of the SC prepared in Example 1, wherein (a) is a N2 adsorption-desorption curve diagram of the SC prepared in step (1) of Example 1, and (b) is a pore size distribution diagram of the SC prepared in step (1) of Example 1;

[0019] Figure 4 is the Fourier transform infrared spectrum (FTIR) of the SC prepared in Example 1;

[0020] Figure 5 is a high-resolution X-ray photoelectron spectroscopy (XPS) spectrum of elements in the SC prepared in Example 1, specifically a high-resolution XPS spectrum of the C element;

[0021] Figure 6 is the electrochemical impedance spectroscopy (EIS) of the SC prepared in Example 1;

[0022] Figure 7 is a diagram showing the change in transmembrane pressure difference of the anaerobic membrane bioreactors R1 and R2 in Example 2;

[0023] Figure 8 The graphs of the COD concentration and COD removal rate of the effluent of the anaerobic membrane bioreactor in Example 2 of the present invention are shown in Figure 2, wherein (a) is a graph of the COD concentration and COD removal rate of the effluent of the blank group R1, and (b) is a graph of the COD concentration and COD removal rate of the effluent of the carbon addition group R2;

[0024] Fig. 9 The graphs of biogas production and CH4 production of the anaerobic membrane bioreactor in Example 2 are shown in Figure 2, wherein (a) is a graph of biogas production and CH4 production of the blank group R1, and (b) is a graph of biogas production and CH4 production of the carbon addition group R2;

[0025] Fig.10 The graphs are the concentration changes of protein (PN) and polysaccharide (PS) in the effluent of the anaerobic membrane bioreactor in Example 2 of the present invention, wherein (a) is the concentration change graph of PN and PS in the effluent of the blank group R1, and (b) is the concentration change graph of PN and PS in the effluent of the carbon addition group R2. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solutions in this specification, the technical solutions in the embodiments of this specification will be clearly and completely described below in conjunction with the drawings in the embodiments of this specification. Obviously, the described embodiments are only part of the embodiments of this specification, not all of the embodiments. Based on the embodiments in this specification, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this specification.

[0027] Embodiment 1:

[0028] A method for preparing pyrolytic carbon comprises the following steps:

[0029] (1) drying the sodium citrate particles in an oven at 120° C. for 12 h; then, heating the dried sodium citrate in a tube furnace to 600° C. at a heating rate of 5° C. / min and pyrolyzing for 2 h; then, cooling the temperature to room temperature at a cooling rate of 5° C. / min;

[0030] The product obtained after pyrolysis was first washed with 200 mL of 1 mol / L hydrochloric acid solution, then washed with deionized water until neutral, and finally dried in an oven at 60°C for 24 h to obtain a honeycomb structured carbon material (SC) with a large specific surface area.

[0031] like Figure 2 (a) and Figure 3 As shown in FIG. 1 , the scanning electron microscope image and gas adsorption analysis results of the SC prepared in step (1) of Example 1 reveal its significant microstructural characteristics. It was observed that the pore wall of the SC presents a porous honeycomb structure with rich porosity and a large specific surface area, specifically 301.2551 m 2 / g. In addition, its average pore size is 4.4485nm, which is consistent with the characteristics of mesoporous structure. This unique microstructure provides an ideal surface for the attachment of microorganisms and promotes the ability of microorganisms to perform redox reactions on the SC surface. This characteristic lays the foundation for improving the methane production of anaerobic membrane bioreactors and provides an effective way to break the membrane fouling dilemma.

[0032] Combination Figure 4 FTIR spectrum of SC in Example 1 and Figure 5 This is the high-resolution XPS spectrum of the C element in the SC prepared in Example 1, located at 1627 cm -1 and 672cm -1 The vibration peaks of 1160cm-1 correspond to C=O and C-H bonds, which may be associated with aromatic compounds through functional groups such as ketones, aldehydes or carboxylic acids. -1 and 1110cm -1The absorption peaks of SC correspond to CO (or CC) and CO bonds, respectively, which may exist in the form of quinones and hydroquinones. According to the theory that there are reversible transformations between functional species, phenolic hydroxyl and quinone (CO) can undergo electron-mediated transformation. Therefore, it is speculated that SC may have the function of an electron shuttle and promote the occurrence of direct interspecies electron transfer (DIET).

[0033] like Figure 6 The electrochemical impedance spectroscopy (EIS) of the SC in Example 1 is shown. The arc-shaped pattern in the EIS graph is usually closely related to the conductivity of the material. The results show that the EIS graph of the SC has significant conductivity, which helps to improve the efficiency of the DIET process.

[0034] Embodiment 2:

[0035] This embodiment relates to a method for simultaneously increasing the methane production of an anaerobic membrane bioreactor and alleviating membrane pollution based on the addition of pyrolytic carbon, and the specific steps are as follows:

[0036] In this example, the SC material prepared in Example 1 was used in an anaerobic membrane bioreactor. The experiment was set up to compare the performance of two groups of anaerobic membrane bioreactors: one group was a control group (R1) without adding SC material, and the other group was an experimental group (R2) with adding SC material.

[0037] According to the experimental design, peristaltic pumps were used to precisely control the inlet and outlet flow rates of the two reactors to ensure that the R1 and R2 reactors were started at the same time. The inlet matrix of the two reactors was artificial simulated wastewater. At the beginning of the experiment, the pre-prepared SC material was added to the R2 reactor to optimize its treatment performance.

[0038] During the operation of the reactor, the effluent water quality indicators and CH4 production changes are recorded regularly, and the inlet COD concentration is gradually increased. At the same time, by combining the magnetic stirring system with the gas aeration device, the pollution of the reactor membrane is reduced and the TMP changes of the reactor are monitored.

[0039] Furthermore, in order to improve the operating efficiency of the reactor, the peristaltic pump is equipped with a time relay for controlling the working and stopping time of the water inlet peristaltic pump and the water outlet peristaltic pump, thereby effectively reducing the degree of membrane pollution.

[0040] The SC material is obtained by pyrolysis of dried sodium citrate. The preparation process is as follows: heating to 600°C at a heating rate of 5°C / min, and pyrolyzing at this temperature for 2-4h; then cooling to room temperature at a cooling rate of 5°C / min, and finally obtaining a carbon material with a honeycomb structure. The dosage of SC is set to 0.3-2g / L in order to achieve the best membrane fouling mitigation effect.

[0041] The influent matrix of the anaerobic membrane bioreactor is stored in a 4°C refrigerator. The artificial simulated wastewater consists of NH4Cl, KH2PO4, NaHCO3 and required trace elements, wherein the carbon-nitrogen-phosphorus ratio is set to 100-300:5:1 to ensure that the nutrients in the reactor are sufficient to meet the growth requirements of anaerobic microorganisms.

[0042] During the entire operation of the reactor, the magnetic stirrer and the gas circulation pump are regularly combined to work together to reduce the degree of membrane fouling and maintain the mixing uniformity in the reactor, thereby improving its processing efficiency.

[0043] The operating conditions for gradually increasing the influent COD concentration are: ensuring that the pH value of the reactor effluent is stably maintained in the range of 6.8 to 8.0 for 10-20 days, and the effluent COD concentration is stably maintained between 0 and 200 mg / L for 10-20 days, so as to verify the long-term operation stability of the reactor and the tolerance to membrane fouling.

[0044] This example demonstrates the effectiveness of adding pyrolytic carbon materials to anaerobic membrane bioreactors, which can significantly alleviate membrane fouling and improve the overall treatment efficiency of the system. This provides important data support and theoretical basis for subsequent research and practical applications, and emphasizes the wide application potential of pyrolytic carbon materials in the field of pollution control.

[0045] Embodiment 3:

[0046] This embodiment further illustrates the implementation method of the present invention by combining a specific example of using an anaerobic membrane bioreactor. The specific steps are as follows:

[0047] (1) Under laboratory conditions, two groups of anaerobic membrane bioreactors with exactly the same appearance, structure and configuration were operated, one of which was a control group reactor without the addition of SC (R1), and the other was an experimental group reactor with the addition of SC (R2).

[0048] (2) A peristaltic pump is used to complete the water inlet and outlet settings of the reactor, and the inlet matrix is ​​artificial simulated wastewater.

[0049] (3) During the operation of the reactor, the effluent water quality indicators and CH4 production changes were recorded regularly, and the inlet COD concentration was gradually increased. At the same time, the magnetic stirring system and aeration device were used in coordination to alleviate membrane fouling and monitor the TMP changes of the reactor.

[0050] Further explanation, the specific structure of the anaerobic membrane bioreactor in step (1) is as follows Figure 1As shown, it consists of membrane components, aeration system and anaerobic digestion reactor. The whole system includes membrane components, completely mixed anaerobic reactor, water inlet barrel, heating barrel, peristaltic pump and wet gas flow meter. The heating barrel is used to control the internal environment temperature of the reactor at about 35°C and ensure that the effective working volume of AnMBR is 3L. The membrane component used is a homemade flat membrane, the membrane material is PVDF, the average pore size is 0.05μm, and the effective filtration area is 0.0288m 2 In addition, a wet gas flow meter was used to measure the volume of biogas produced, and a membrane pressure gauge was used to monitor membrane pressure changes in real time.

[0051] In a further embodiment, the SC material added to the R2 reactor in step (1) is the pyrolytic carbon prepared in Example 1, and the dosage is set to 0.5 g / L. The formula of artificial simulated wastewater consists of NH4Cl, KH2PO4, NaHCO3 and trace elements, wherein the carbon-nitrogen-phosphorus ratio is 200:5:1. When the influent COD concentration is 2000mg / L, the specific ratio of trace elements is: NaCl: 1mg / L; CuCl2·5H2O: 0.5mg / L; CaCl2: 5mg / L; ZnCl2: 0.5mg / L; FeCl2: 2.5mg / L; EDTA: 2.5mg / L; MgCl2·6H2O: 10mg / L; CoCl·6H2O: 0.5mg / L; MnCl2·4H2O: 0.5mg / L; AlCl3: 0.25mg / L; NiCl·6H2O: 0.5mg / L; H3BO4: 0.5mg / L; (NH4)6Mo6O 24 4H2O:1.5mg / L.

[0052] In step (2), the frequency and volume of the inlet and outlet substrates are automatically controlled by a time relay and a peristaltic pump. During the startup phase of the two reactors, the initial COD concentration of the influent substrate was set to 2000 mg / L, and the peristaltic pumps for the inlet and outlet substrates were set to operate for 8 min and stop for 2 min, so as to control the hydraulic retention time of the two reactors to 24 h.

[0053] In a further scheme, in step (3), the effluent water quality indicators include but are not limited to pH, effluent COD concentration, effluent PN concentration, effluent PS concentration, etc. Experiments have shown that when the effluent pH value of the reactor is stable between 6.8-8.0 for 10-20 days, and the effluent COD concentration is stable at 0-200 mg / L for 10-20 days, the influent COD concentration can be gradually increased; the influent COD concentration of the two groups of reactors in the embodiment is set to the following stages: 1-15d: 2000 mg / L; 16-25d: 3000 mg / L; 25-40d: 4000 mg / L; 40-54d: 5000 mg / L; 54-70d: 6000 mg / L; 71-90d: 7000 mg / L; 91-120d: 8000 mg / L, and the total operation time of the reactor is 120d.

[0054] In a further embodiment, in step (3), in order to analyze the production of CH4 and CO2, gas chromatography is used to monitor the relative content of the gases, and the drainage gas collection method is used to evaluate the total gas production of the reactor.

[0055] In a further solution, in step (3), as the organic load increases, the TMP variation trend of the reactor is monitored, and the membrane operation strategy is set to run for 7 minutes and stop for 3 minutes to alleviate membrane fouling.

[0056] like Figure 2 As shown, SEM images of anaerobic sludge from two groups of reactors R1 and R2 in Example 3 at 40 days and 120 days of operation are shown. The results show that when the reactor was running for 40 days, the addition of SC material had a significant effect on the morphology of anaerobic particles in the R2 reactor. Compared with the control group R1, the surface of the particles in R2 showed more obvious curling characteristics. In addition, the flocculent sludge observed in the R2 reactor combined with the encapsulation effect of SC promoted the electron transfer process between microorganisms, which may enhance the overall metabolic function of the reactor. When the reactor was running for 120 days, most of the microorganisms in the R2 reactor showed a spherical morphology, while the microorganisms in the R1 reactor mainly showed a rod-shaped morphology. This phenomenon shows that the introduction of SC not only improves the structural characteristics of the sludge, but also may enhance the metabolic activity of the microbial community, thereby improving the overall performance of the reactor.

[0057] like Figure 7 The figure shows the changes in TMP of anaerobic membrane bioreactors R1 and R2. The TMP value of the membrane module of the control group R1 reached 10kPa when it was running for 20 days, while the TMP value of the membrane module of the R2 reactor with SC added remained stable within 5kPa; until the reactor was running for 75 days, the TMP of the membrane module of R2 rose to 10kPa. This result shows that the addition of SC significantly slowed down the accumulation of pollutants on the membrane surface, thereby extending the effective operation time of the membrane module.

[0058] During the process of increasing the organic load (OLR) of the reactor, the COD concentration of the AnMBR effluent after adding SC showed higher stability compared with the control group, and the COD removal effect of the R2 reactor was better than that of the R1 reactor, with a removal rate of up to 99.39% (see Figure 8 ). In addition, the cumulative production and proportion of CH4 in the AnMBR with pyrolytic carbon were higher than those in the control group. Specifically, the cumulative production of CH4 was about 1.58 times that of the control group. In each experimental stage, the biogas production of R1 and R2 was between 500-4000mL / d, and the proportion of CH4 in the biogas was maintained between 56.47% and 66.7%. Although the two reactors performed similarly in terms of organic matter removal (see Fig.10 ), but there are significant differences in their methane production capacity (see Fig. 9 ). Specifically, when the organic loading rate was 3.5, 7.5, 8.5 and 10.0 gCOD / (L·d), the specific methanogenesis rate of the control group R1 was 188 mL CH4 / g COD, 340 mL CH4 / g COD, 771 mL CH4 / g COD and 1002 mL CH4 / g COD, respectively, while the reactor R2 operated under the condition of adding SC showed a higher specific methanogenesis rate, which was 223 mL CH4 / g COD, 825 mL CH4 / g COD, 1524 mL CH4 / gCOD and 1413 mL CH4 / g COD, respectively. These results show that the addition of SC can significantly improve the ability of microorganisms in the reactor to process organic matter and produce methane, thereby improving the overall operating performance of the anaerobic membrane bioreactor. The introduction of SC as a conductive material in the anaerobic membrane bioreactor not only effectively reduces membrane fouling, but also extends the service life of the membrane assembly to 6 times. The preparation process of SC is simple and low-cost. Adding an appropriate amount can achieve significant treatment benefits. Its good conductivity promotes electron transfer between microbial species, thereby increasing methane production by 1.39 times.

[0059] Therefore, the application of SC (pyrolytic carbon) as a conductive material in AnMBR systems shows the potential to effectively solve the problem of membrane fouling. The conductive properties of pyrolytic carbon can promote the transfer of electrons, thereby enhancing the metabolic activity of anaerobic microorganisms and improving their ability to degrade pollutants. This enhanced metabolic activity helps to reduce the deposition of sludge and the formation of biofilms on the membrane surface, thereby reducing the frequency of membrane fouling. In addition, the porous structure of pyrolytic carbon provides a larger specific surface area, which facilitates the attachment and growth of microorganisms and further optimizes the electron transfer process. This not only improves the wastewater treatment efficiency and gas production rate, but also provides important technical support for the construction of an AnMBR wastewater treatment system that is both environmentally friendly and efficient.

[0060] In summary, the technical solution of the present invention can include the following beneficial effects:

[0061] Introducing SC as a conductive material in an anaerobic membrane bioreactor not only effectively slows down membrane pollution, but also extends the service life of the membrane assembly to 6 times. The preparation process of SC is simple and low-cost, and adding an appropriate amount can achieve significant treatment benefits. Its good conductivity promotes electron transfer between microbial species, thereby increasing methane production by 1.39 times, significantly improving the anaerobic digestion efficiency of microorganisms, and realizing resource utilization of sewage treatment; the present invention uses gradient temperature pyrolysis technology to convert sodium citrate into SC with a honeycomb structure, and adds it to the sewage anaerobic treatment system, which can significantly increase the methane production of the microbial anaerobic digestion system, mainly due to the good biocompatibility, rapid mass transfer capacity and electron transfer capacity of SC.

[0062] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for improving the efficiency of anaerobic membrane bioreactor and alleviating membrane fouling by using pyrolytic carbon, characterized in that: During the start-up phase of the anaerobic membrane bioreactor, a conductive material SC is added into the reactor to carry out anaerobic digestion reaction. The conductive material SC is a carbon material with a honeycomb structure obtained by pyrolysis of sodium citrate at elevated temperature.

2. The method according to claim 1, characterized in that The effective working volume of the anaerobic membrane bioreactor was 3.5 L, and the internal temperature was maintained at 35-37°C.

3. The method according to claim 1, characterized in that The added amount of the conductive material SC is 0.5 g / L of the volume of the sludge mixed liquid in the reactor, and the water content of the sludge is 86.29%.

4. The method according to claim 1, characterized in that The heating rate of the sodium citrate pyrolysis is 5°C / min. After heating to 600°C, the pyrolysis is carried out for 2-4h, and then cooled to room temperature at a cooling rate of 5°C / min.

5. The method according to claim 1, characterized in that After the conductive material SC is obtained by pyrolysis at elevated temperature, it is first washed with a hydrochloric acid solution having a concentration of 0.8-1.2 mol / L, then washed with deionized water until neutral, and then dried.

6. The method according to claim 1, characterized in that The method uses artificial simulated wastewater as an influent reaction matrix. The artificial simulated wastewater is composed of NH4Cl, KH2PO4, NaHCO3 and trace elements and is stored in a refrigerator. The carbon, nitrogen and phosphorus ratio of the artificial simulated wastewater is 100-300:5:

1.

7. The method according to any one of claims 1 to 6, characterized in that: The anaerobic membrane bioreactor is equipped with a self-made flat membrane assembly, the membrane material is polyvinylidene fluoride, the average pore size is 0.05 μm, and the effective filtration area is 0.0288 m 2 .

8. The method according to claim 7, characterized in that The anaerobic membrane bioreactor is equipped with a magnetic stirring system and a gas circulation system for coordinated work.

Citation Information

Patent Citations

  • Device for relieving membrane pollution of electric reinforced separation membrane and synchronously promoting methane production

    CN108483620A

  • Method for enhancing sludge methane conversion and membrane pollution resistance through combination of carbon dots and electric membrane

    CN115448559A

  • 3D honeycomb carbon material and preparation method and application thereof

    CN117246996A

  • Method for promoting membrane pollution resistance of anaerobic membrane bioreactor under action of electric field and application

    CN117446969A

  • Anaerobic membrane bioreactor quality and efficiency improving method based on charcoal addition

    CN117466435A

Cited By

  • Method for enhancing efficiency of anaerobic membrane bioreactor based on nano ferric oxide-biochar composite conductive material

    CN120589926A

  • Magnetic iron-carbon composite material and application thereof in increasing methane yield in anaerobic digestion system

    CN121554099A